2017
DOI: 10.1111/asj.12954
|View full text |Cite
|
Sign up to set email alerts
|

Influences of quorum‐quenching probiotic bacteria on the gut microbial community and immune function in weaning pigs

Abstract: The aim of this study is to investigate the dynamic gut microbial diversity in weaning swine after administering feed supplemented with probiotic bacteria that specifically inhibit the activity of quorum molecules. Initially, the universal quorum molecule autoinducer-2 (AI-2) bioassay results indicated that AI-2 activity was profoundly inhibited in enterohemorrhagic Escherichia coli (EHEC) O157:H7 in the presence of Lactobacillus acidophilus strain 30SC cell extract, although the growth of EHEC was not affecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 29 publications
0
15
0
1
Order By: Relevance
“…A healthy gut microbiome is paramount to adequate systemic immune health. Several studies have demonstrated that microbial supplementation bolsters gut health and immune function in the presence of infection [23][24][25][26][27][28]. Modulation of gut immunity during the critical windows of weaning and creep feeding has the most influence on innate immunity and may maximize pig growth performance [29].…”
Section: Discussionmentioning
confidence: 99%
“…A healthy gut microbiome is paramount to adequate systemic immune health. Several studies have demonstrated that microbial supplementation bolsters gut health and immune function in the presence of infection [23][24][25][26][27][28]. Modulation of gut immunity during the critical windows of weaning and creep feeding has the most influence on innate immunity and may maximize pig growth performance [29].…”
Section: Discussionmentioning
confidence: 99%
“…Disruption of QS signaling may act as an antivirulence approach. For example, the addition of the probiotic Lactobacillus acidophilus to the feed of weaning pigs harboring EHEC in their gut inhibited the activity of AI-2 and prevented biofilm formation, without affecting the growth of EHEC (77). AI may also dictate the presence of a certain microbial species, thereby changing the overall metabolic landscape of the gut.…”
Section: Preventing Initial Colonizationmentioning
confidence: 99%
“…Probiyotik özelliklerin değerlendirilme işlemleri tamamlandıktan sonra, ilgili suşlar in vivo testlere tabi tutulmaktadır (De Melo Pereira et al, 2018). Probiyotiklerle ilgili olarak fare, sıçan ve domuzlarda in vivo testlerin yapıldığı çeşitli çalışmalar mevcuttur (Sarkar et al, 2016;Kim et al, 2018;Walcher et al, 2018). Ancak, çoğu kez artan maliyet ve etik nedenlerden dolayı in vivo testler yapılamamaktadır.…”
Section: Bağırsak Yüzeyine Tutunmaunclassified